BANGUNAN TRADISIONAL KAMPUNG NAGA: BENTUK KEARIFAN WARISAN LELUHUR MASYARAKAT SUNDA - Iwan Hermawan (Sosio-Didaktika: Social Science Education Journal, 2014)
A space is where humans live their lives on earth. Its presence is essential for human life, as sustained or damage to the environment will affect humans who live in it. To this day Kampung Naga village continue to keep their living space preserved as practiced to their houses and other buildings. This paper aims to reveal the Sunda local wisdom contained in building houses in Kampung Naga village. Data collected through surveys, personal involvement, interviews, and literature. The data were analyzed qualitatively. Kampung Naga houses and other buildings are construedted according to the teachings of the ancestors. Shape and architecture of the building adapts to local conditions. For them life is not in nature but living with nature. These values are noble values that need to be maintained and actualized in everyday life of modern humans in protecting the environment.